Test rig design for automotive refrigeration system [electronic resource] - Ahmad Zulkhairie Amran, author 643290 (2014)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014